Mechanische und Strömungsmechanische Topologieoptimierung mit der Phasenfeldmethode - Selzer, Michael (KIT Scientific Publishing, 2022)
In engineering work, the optimization of the microstructure of a material, of mechanically loaded components and of components influencing the flow behaviour is important. Understanding the behavior of flows in geological structures can be used to optimize the design of geothermal power plants. In this thesis, methods from continuum mechanics, fluid mechanics and the phase field method are presented for the optimization of such processes and examples of optimizations are shown.